Initial Effects of Prescribed Burning on Survival and Nesting Success of Northern Bobwhites in West-Central Texas - Philip S. Carter; Dale Rollins; Cody B. Scott (National Quail Symposium Proceedings, 2017)
Fire is often prescribed for managing habitat for northern bobwhites (Colinus virginianus) in the southeastern United States, yet little is known about its use as a tool in more xeric portions of the species’ range. This study was conducted from 1994 to 1995 on 3 sites in the northern Edwards Plateau ecoregion of Texas to monitor immediate post-burn effects on bobwhite ecology. Each site included a burned pasture paired with an unburned control. We radiomarked >= 50 bobwhites (25/pasture) at each study site with neck-loop transmitters just prior to burning and monitored their survival and nesting habits for 6 months post-burn. Survival was similar (P > 0.05) between burned and unburned areas. Predation was the leading cause of mortality, with mammals and raptors accounting for 68% and 31% of the predation, respectively. Nest initiation and success were low for both treatments. Nest sites occurred mostly in association with prickly pear cactus (Opuntia spp.). Our results suggest that relatively ‘‘cool’’ prescribed burns had few short-term effects on bobwhite survival in west-central Texas. However, reductions in cacti density and cover that often occur post-burn, especially if followed by an application of herbicide (i.e., picloram), may reduce the number of potential nesting sites for bobwhites.
Keywords: burning; cacti; Colinus virginianus; mortality; nesting; northern bobwhite; prickly pear; range management; telemetry; Texas